PENGARUH KUALITAS LAYANAN DAN CITRA MEREK TERHADAP LOYALITAS MELALUI KEPUASAN NASABAH PERUM PEGADAIAN CABANG BEKASI TIMUR - Arry Dwi Syahputra (Jurnal Ekonomi dan Industri, 2020)
This study aims to analyze the effect of service quality and brand image on customer loyalty through customer satisfaction at Perum Pegadaian Timur Bekasi Branch. The study was conducted at Perum Pegadaian Timur Bekasi Branch. Sampling of research using probability sampling and simple random sampling methods. Data analysis uses path analysis. Based on data analysis, it is known that partially each of the independent variables is service quality, brand image and customer satisfaction has an influence on customer loyalty at Perum Pegadaian, East Bekasi Branch. Then the results of the analysis of customer satisfaction variables as intervening variables can be proved perfectly that customer satisfaction variables indirectly influence the service quality variable on customer loyalty and brand image variables on customer loyalty. This statement can be proven by the magnitude of the indirect effect (service quality on customer loyalty and brand image on customer loyalty) through customer satisfaction identified as an intervening variable.